Epizootic study of IBD in chickens during the years 1990-1998 in North Greece - BOUGIOUKLIS (Π. ΜΠΟΥΠΟΥΚΛΗΣ) P.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) I.; IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
This report concerns an epizootic study of IBD in chickens reared in North Greece, during the years 1990-1998. The frequency of IBD was determined according to year, month and productive direction. The clinical cases were studied from the Clinic of Poultry Diseases (Faculty of Veterinary Medicine, Aristotle University of Thessaloniki) during the years 1990-1998. An increase of IBD cases was determined in 1992, 1993, 1994, 1996 and 1997. Also, an increase of IBD cases was observed during the Spring and Summer months. A higher frequency of IBD was observed on broilers.